(untitled) (Culturas Científicas, 2018)
The paper explores the methodological similarities between Charles Darwin and the duo Karl Marx-Friedrich Engels. Although there are many differences between the British evolutionist and German revolutionaries, all defend materialistic theories that emphasize the universal movement of the universe. Furthermore, both approaches have been developed in the same period so that we can encounter common elements. In other to pin point such common elements, I focus on the Darwinian thesis on common ancestor, the biogeographical explanation and the morphological, embryological, and paleontological evidences of evolution in connection with the continuity principle. Then, on Marx and Engels, I identify the application of the dialectical principle about the change from quantity to quality, interpenetration of the opposites, and the double negation. I also criticize reductionist approaches to science, especially in the theory of evolution, and argue that the reactionary element of Darwinism lies in its support to the Malthusian thesis of political economy. Finally, I argue that the interdisciplinary approach of Darwin is limited by his reductionist and Malthusian convictions. It is possible to overcome this limitation through the formulation of a dialectical interdisciplinary science.